Mineral paragenesis of olmiite/poldevaartite and rhodochrosite/shigaite occurrences in the Kalahari Manganese Field, and their relation to the formation of high-grade manganese ore of Nchwaning II mine, Black Rock, South Africa - Opperman, Alicia (Rhodes University, Faculty of Science, Department of Geology)
Access restricted. Access embargoed until 2025.
Keywords: Uncatalogued